Coaching leadership: leaders' and followers' perception assessment questionnaires in nursing - Maria Lúcia Alves Pereira Cardoso; Laís Helena Ramos; Maria D’Innocenzo (Einstein (São Paulo))
Objective : To describe the development, content analysis, and reliability of two questionnaires to assess the perception of nurse leaders, nurse technicians, and licensed practical nurses − coached in the practice of leadership and the relation with the dimensions of the coaching process. Methods : This was a methodological study with a quantitative and qualitative approach, which had the goal of instrumentation in reference to the construction and validation of measuring instruments. The instrument proposition design was based on the literature on leadership, coaching, and assessment of psychometric properties, subjected to content validation as to clarity, relevance, and applicability in order to validate the propositions through the consensus of judges, using the Delphi technique, in 2010. The final version of the questionnaires was administered to 279 nurses and 608 nurse technicians and licensed practical nurses, at two university hospitals and two private hospitals. Results : The Cronbach’s alpha value with all items of the self-perception instrument was very high (0.911). The team members’ instrument of perception showed that for all determinants and for each dimension of the coaching process, Cronbach’s overall alpha value (0.952) was considered quite high, pointing to a very strong consistency of the scale. Confirmatory analysis showed that the models were well adjusted. Conclusion : From the statistical validation we compared the possibility of reusing the questionnaires for other study samples, because there was evidence of reliability and applicability.